The effect of exercise training on mediators of inflammation in breast cancer survivors: A systematic review with meta-analysis (2016)
Several sources of evidence indicate that exercise during and after breast cancer could positively modulate the tumor microenvironment. This meta-analysis aimed to determine the effects of exercise training on mediators of inflammation in breast cancer survivors. We searched for randomized controlled trials published from January 1990 to March 2014. An inverse variance method of meta-analysis was performed using a random effects model in the presence of statistical heterogeneity. Eight high-quality trials (n = 478) were included. Exercise improved the serum concentrations of IL6 [weighted mean difference (WMD) = -0.55 pg/mL; 95% confidence interval (CI), -1.02 to -0.09], TNF? (WMD = -0.64 pg/mL; 95%CI, -1.21 to -0.06), IL8(MD= -0.49 pg/mL; 95% CI, -0.89 to -0.09), and IL2 (WMD = 1.03 pg/mL; 95% CI, 0.40 to 1.67). No significant differences were found in the serum concentrations of C-reactive protein (WMD = -0.15; 95% CI, -0.56 to 0.25) or IL10 (WMD = 0.41; 95% CI, -0.18 to 1.02). Exercise training positively modulates chronic low-grade inflammation in women with breast cancer, which may impact upon carcinogenic mechanisms and the tumor microenvironment. These findings align with the other positive effects of exercise for breast cancer survivors, reinforcing the appropriateness of exercise prescription in this population. © 2016 American Association for Cancer Research.